Pengaruh Transparansi, Kepercayaan, Persepsi Kemudahan dan Tingkat Pendapatan terhadap Minat Muzzaki dalam membayar Zakat secara Online (Studi Kasus pada Muzzaki di Kota Semarang) - Siska Adelia Putri; Zainal Alim Adiwijaya (Politeknik Raflesia Press, 2025)
— This study aims to analyze the influence of transparency, trust, perceived ease, and income level on muzakki's interest in paying zakat online, with a case study on muzakki in Semarang City. This study uses a quantitative approach with an explanatory research method. The sample selection method in this study uses a purposive sampling technique. The data source used in this study uses primary data, conducted through a survey obtained by distributing questionnaires via Google Form to respondents. Respondents in this study were muzakki who are domiciled or reside in Semarang City. The measurement scale used is the linkert scale with a score of 1-5. The analysis technique used to test the hypothesis and process the data is multiple linear regression analysis using the SPSS version 26 application. The results of the study showed that the variables of transparency, trust, and income level did not affect muzakki's interest in paying zakat online, while the variable of perceived ease showed an effect on muzakki's interest in paying zakat online.